(3GdefSc GdKGfjs - (3GdHMQGfj GdeGMhRj, GHf YeGQ, GHf YeGQ GdHMQGfj, SdjeGf Hf YHO Gddg Hf Ydj, J (B1121(3g` (B1709(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3HYO GdMeO hGdUdhI, abO SCdfj HYV GdENhGf aj Gddg JCdja QSGdI hLjRI aj efGSc GdML GbJUQ ajgG Ydi eG XgQ dj eOQcg hhVM YfOj eSdcg, aCbhd(B: .. (3GdML dZI(B: (3GdbUO, hTQYG(B: (3GSe dLejY GdefGSc GdeDOGJ aj GdejbGJ hecI hGdeTGYQ Ch McegGs
(3BNQgG (B:s
(3BNQgG(B: (3hdPdc cGfJ RjGQI bHhQge (B.. (3dajVGf CfhGQ cKjQI efge Ydi GdRGFQjf ceG jTGgO CUMGH GdHUGFQ IjTgOhf Hg ceG TgO Hg ZjQ hGMO ef aMhd GdeMbbjf, hGdCNHGQ GdhGQOI HKhGH RjGQJg hRjGQI Cgd HjJg cKjQI eTghQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 128s
(3GdPQjYI, L (B22: 166s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis